Precontractual duty to inform the surety - Dabić Snežana (Anali Pravnog Fakulteta u Beogradu)
Sureties often claim that they have not been informed about the difficult financial situation of the principal debtor prior to the conclusion of the contract and that they have been the victims of a fraud. Usually, it is the debtor who is responsible for the fraud: he is interested in concealing or even improving his real financial situation. However, the surety contract is concluded between the surety and the creditor. Is the surety in a position to annul the contract if the deceit is practiced by a third party? On the other side, creditors (especially, banks) often possess the exact information about the financial capacity of the debtor: should they inform the surety about this? And what are the consequences if they do not? Can the surety ask for the annulment of the contract on the basis of creditor's non-disclosure?.